The Influence of Motivation, Performance Appraisal, and Work Environment on Employee Performance at the Kecamatan Semarang Barat Office - Hendro Cahyono; Bayu Kurniawan; Hawik Ervina Indiworo (Departement of Mathematics Education, 2024)
This study aims to analyze the effect of work motivation and work environment on employee performance at the West Semarang District Office. The research method used is a quantitative approach with regression analysis. The population in this study is all employees in the West Semarang District Office, which amounts to 170 people. The sampling technique uses a saturated sample method, where all members of the population are used as research samples. The results showed that Work motivation has a negative and significant effect on employee performance. Any increase in work motivation actually has the potential to reduce employee performance. Performance appraisal has a positive and significant impact on employee performance. When the value of performance appraisal increases, employee performance also tends to increase, although not too strongly. The work environment has a negative but not significant effect on employee performance. There is not enough statistical evidence to suggest the work environment affects performance. Work motivation, performance appraisal, and work environment simultaneously have a significant effect on employee performance. In conclusion, to improve employee performance, organizations need to pay attention to employee motivation factors and an effective performance appraisal system. Although the work environment is partially not proven to be influential, simultaneously with other factors, it still has an impact on employee performance at the West Semarang District Office.